Solar Cells
By using MeO-TFATA as a hole transport material in tin-based perovskite solar cells, the problem of low photoelectric conversion efficiency caused by interface defects is solved, and efficient photoelectric conversion is achieved.
Patent Information
- Application Number
- CN202080070465.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-18
- Filing Date
- 2020-07-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-07-03
AI Technical Summary
The photoelectric conversion efficiency of existing tin-based perovskite solar cells is low, mainly due to defects at the interface between hole transport materials and tin-based perovskite compounds.
4,4′,4″-tris[9,9-dimethyl-2-fluorenyl(4-methoxyphenyl)amino]trianyl (MeO-TFATA) is used as the hole transport material, and a hole transport layer is formed on the photoelectric conversion layer by spin coating or printing to reduce the interfacial defect density.
The photoelectric conversion efficiency of tin-based perovskite solar cells is improved and efficient photoelectric conversion is achieved.
Smart Images

Figure CN114556604B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solar cells. Background Art
[0002] In recent years, perovskite solar cells are being studied and developed. 3 A perovskite compound represented by (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) is used as a photoelectric conversion material.
[0003] A lead-free perovskite solar cell is proposed in Non-Patent Document 1. In the lead-free perovskite solar cell disclosed in Non-Patent Document 1, a perovskite solar cell having a chemical formula of CsSnI 3 Perovskite compounds, TiO 2 and Spiro-OMETAD were used as photoelectric conversion materials, electron transport materials, and hole transport materials, respectively.
[0004] A dye-sensitized solar cell is disclosed in Patent Document 1. The dye-sensitized solar cell disclosed in Patent Document 1 has at least one organic hole conductor material (ie, hole transport material). Patent Document 1 discloses various materials including Spiro-OMETAD as the organic hole conductor material.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2014-520386
[0008] Non-patent literature
[0009] Non-patent document 1: Mulmudi Hemant Kumar et al., "Lead-free halide perovskitesolar cells with high photocurrents realized through vacancy modulation", Advanced Materials, 2014, Volume 26, Issue 41, 7122-7127. Summary of the invention
[0010] Problems to be solved by the invention
[0011] An object of the present disclosure is to provide a tin-based perovskite solar cell having high photoelectric conversion efficiency.
[0012] Means for solving problems
[0013] The solar cell disclosed herein has:
[0014] 1st electrode;
[0015] The second electrode;
[0016] a photoelectric conversion layer disposed between the first electrode and the second electrode; and
[0017] a hole transport layer disposed between the first electrode and the photoelectric conversion layer,
[0018] wherein at least one electrode selected from the first electrode and the second electrode has light-transmitting property,
[0019] The photoelectric conversion layer contains a perovskite compound composed of monovalent cations, divalent cations and halogen anions.
[0020] The monovalent cation contains at least one selected from the group consisting of a formamidinium cation and a methylammonium cation,
[0021] The divalent cations include Sn cations,
[0022] The halogen anion comprises an iodide ion, and
[0023] The hole transport layer contains 4,4',4"-tris[9,9-dimethyl-2-fluorenyl(4-methoxyphenyl)amino]triphenylamine.
[0024] Effects of the Invention
[0025] The present disclosure provides a tin-based perovskite solar cell with high photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a cross-sectional view showing a solar cell according to an embodiment. DETAILED DESCRIPTION
[0027] <Definition of Terms>
[0028] The term "perovskite compound" used in this specification refers to a compound having the chemical formula ABX 3 (wherein A is a monovalent cation, B is a divalent cation and X is a halogen anion) and a perovskite crystal structure having a crystal similar thereto.
[0029] The term "perovskite solar cell" used in this specification refers to a solar cell containing a perovskite compound as a photoelectric conversion material.
[0030] The term "tin-based perovskite compound" used in this specification refers to a perovskite compound containing tin.
[0031] The term "tin-based perovskite solar cell" used in this specification refers to a solar cell containing a tin-based perovskite compound as a photoelectric conversion material.
[0032] The term "lead-based perovskite compound" used in this specification refers to a perovskite compound containing lead.
[0033] The term "lead perovskite solar cell" used in this specification refers to a solar cell containing a lead-based perovskite compound as a photoelectric conversion material.
[0034] <Understanding that forms the basis of the present disclosure>
[0035] The following describes the findings that form the basis of the present disclosure.
[0036] It is known that, generally speaking, the energy difference between the HOMO energy level of the hole transport material and the energy level at the upper end of the valence band of the photoelectric conversion material leads to a decrease in the photoelectric conversion efficiency of the solar cell. The value of the "energy level at the upper end of the valence band" in this specification is a value based on the vacuum energy level.
[0037] At present, representative examples of hole transport materials used in perovskite solar cells are poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA") or 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene (hereinafter referred to as "Spiro-OMeTAD"). The HOMO energy level of these hole transport materials matches the energy level at the upper end of the valence band of the lead-based perovskite compound (i.e., -5.4 eV). That is, the energy difference between the HOMO energy level of these hole transport materials and the energy level at the upper end of the valence band of the lead-based perovskite compound is small.
[0038] On the other hand, the energy level at the upper end of the valence band of the tin-based perovskite compound is about 0.5 eV shallower than that of the lead-based perovskite compound. 2 ) 2 Sn 3 The energy level at the upper end of the valence band is -4.9 eV. Therefore, in tin-based perovskite solar cells, it is necessary to use a hole transport material with a shallower HOMO energy level than in lead-based perovskite solar cells.
[0039] The present inventors have further discovered that even when a hole transport material having a HOMO level with a small energy difference from the energy level at the upper end of the valence band of the tin-based perovskite compound is used, the photoelectric conversion efficiency of the solar cell cannot be improved. It is believed that one of the causes of this problem is that the tin-based perovskite compound has defects at the interface between the hole transport material and the tin-based perovskite compound.
[0040] After repeated studies, the inventors have newly discovered that the photoelectric conversion efficiency of tin-based perovskite solar cells can be improved by using 4,4′,4″-tri[9,9-dimethyl-2-fluorenyl(4-methoxyphenyl)amino]triphenylamine (hereinafter referred to as “MeO-TFATA”) as a hole transport material.
[0041] Based on the above findings, the present inventors provide a solar cell containing a tin-based perovskite compound and having high photoelectric conversion efficiency.
[0042] <Embodiments of the present disclosure>
[0043] Below, while referring to the attached Figure 1 The embodiments of the present disclosure will be described in detail.
[0044] Figure 1 FIG. 1 shows a cross-sectional view of a solar cell 100 according to this embodiment. Figure 1 As shown, the solar cell 100 of the present embodiment includes: a first electrode 7 ; a second electrode 2 ; a photoelectric conversion layer 5 provided between the first electrode 7 and the second electrode 2 ; and a hole transport layer 6 provided between the first electrode 7 and the photoelectric conversion layer 5 .
[0045] The first electrode 7 is opposed to the second electrode 2 in the following manner: the hole transport layer 6 and the photoelectric conversion layer 5 are located between the first electrode 7 and the second electrode 2. At least one electrode selected from the first electrode 7 and the second electrode 2 has light transparency. In this specification, the term "electrode has light transparency" means that 10% or more of light at any wavelength of light having a wavelength of 200nm to 2000nm is transmitted through the electrode.
[0046] (Photoelectric conversion layer 5)
[0047] The photoelectric conversion layer 5 contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions as a photoelectric conversion material. The photoelectric conversion material is a light absorbing material.
[0048] In this embodiment, the perovskite compound may be a compound having the chemical formula ABX 3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion).
[0049] According to the commonly used expressions for perovskite compounds, in this specification, A, B and X are also referred to as A site, B site and X site, respectively.
[0050] In this embodiment, the perovskite compound may have a chemical formula of ABX 3The perovskite crystal structure is represented by . For example, a monovalent cation is located at the A site, a divalent cation is located at the B site, and a halogen anion is located at the X site.
[0051] (A site)
[0052] The monovalent cation at the A site comprises a formamidinium cation (i.e., NH 2 CHN 2 +) and methylammonium cations (i.e. CH 3 NH 3 + By making the A site contain at least one selected from the group consisting of a formamidinium cation and a methylammonium cation, a tin-based perovskite solar cell having a high photoelectric conversion efficiency can be obtained.
[0053] In order to improve the photoelectric conversion efficiency of solar cells, the monovalent cation at the A site may also contain a guanidinium cation (i.e., CH 6 N 3 + ). The monovalent cation at the A site may also contain other monovalent cations in addition to the formamidinium cation, the methylammonium cation and the guanidinium cation. Examples of other monovalent cations are organic cations or alkali metal cations. Examples of organic cations are phenethylammonium cations (i.e., C 6 H 5 C 2 H 4 NH 3 +) The alkali metal cation is, for example, a cesium cation (i.e., Cs + ).
[0054] The phrase “the A site mainly contains at least one selected from the group consisting of formamidinium cations and methylammonium cations” means that the molar ratio of the total molar number of formamidinium cations and methylammonium cations to the total molar number of monovalent cations exceeds 50%.
[0055] The A site may be substantially composed of at least one selected from the group consisting of a carbamidinium cation and a methylammonium cation. The phrase "the A site is substantially composed of at least one selected from the group consisting of a carbamidinium cation and a methylammonium cation" means that the molar ratio of the total number of moles of the carbamidinium cation and the number of moles of the methylammonium cation to the total number of moles of the monovalent cations is 90% or more, preferably 95% or more.
[0056] The A site may also mainly contain carboxamidinium cations. The so-called "the A site mainly contains carboxamidinium cations" means that the ratio of the molar number of carboxamidinium cations to the total molar number of monovalent cations is the highest. The A site may also be substantially composed of carboxamidinium cations only. The so-called "the A site substantially consists of carboxamidinium cations only" means that the molar ratio of the molar number of carboxamidinium cations to the total molar number of monovalent cations is 90% or more, preferably 95% or more.
[0057] (Site B)
[0058] The divalent cation at the B site contains Sn cation, i.e. Sn 2+ The divalent cations may contain 50 mol% or more of Sn cations. The phrase "the divalent cations contain 50 mol% or more of Sn cations" means that the molar ratio of the amount of Sn cations to the total amount of the divalent cations is 50% or more. The divalent cations may also consist of only Sn.
[0059] (X site)
[0060] The halogen anion at the X site contains an iodide ion. By making the X site contain an iodide ion, a tin-based perovskite solar cell with high photoelectric conversion efficiency can be obtained. The halogen anion at the X site can be composed of two or more halogen ions.
[0061] The X site may mainly contain iodide ions. The so-called "halogen anions mainly contain iodide ions" means that the ratio of the molar number of iodide ions to the total molar number of halogen anions is the highest. The X site may be substantially composed of iodide ions only. The so-called "X site is substantially composed of iodide ions only" means that the molar ratio of the molar number of iodide ions to the total molar number of anions is 90% or more, preferably 95% or more.
[0062] The photoelectric conversion layer 5 may also contain materials other than the photoelectric conversion material. For example, the photoelectric conversion layer 5 may also contain a quencher substance for reducing the defect density of the perovskite compound. The quencher substance is a fluorine compound such as tin fluoride. The molar ratio of the quencher substance to the photoelectric conversion material may be 5% to 20%.
[0063] The photoelectric conversion layer 5 may mainly contain a perovskite compound composed of monovalent cations, divalent cations including Sn cations, and halogen anions.
[0064] The so-called "photoelectric conversion layer 5 mainly contains a perovskite compound composed of monovalent cations, divalent cations including Sn cations and halogen anions" means that the photoelectric conversion layer 5 contains more than 70 mass% (preferably more than 80 mass%) of a perovskite compound composed of monovalent cations, divalent cations including Sn cations and halogen anions.
[0065] The photoelectric conversion layer 5 may contain impurities. The photoelectric conversion layer 5 may further contain compounds other than the above-mentioned perovskite compound.
[0066] The photoelectric conversion layer 5 may have a thickness of 100 nm to 10 μm, preferably 100 nm to 1000 nm. The thickness of the photoelectric conversion layer 5 depends on the light absorption thereof.
[0067] (Hole Transport Layer 6)
[0068] The hole transport layer 6 contains MeO-TFATA represented by the following structural formula (1) as a hole transport material.
[0069]
[0070] MeO-TFATA has a HOMO energy level with a small energy difference with the energy level at the upper end of the valence band of the tin-based perovskite compound. In addition, it is believed that MeO-TFATA is not easy to produce defects at the interface with the tin-based perovskite compound. That is, it is believed that the interface between the hole transport layer 6 containing MeO-TFATA and the photoelectric conversion layer 5 containing the tin-based perovskite compound has a small defect density. Therefore, by making the hole transport layer 6 contain MeO-TFATA, the solar cell 100 containing the tin-based perovskite compound has a high photoelectric conversion efficiency.
[0071] The hole transport layer 6 may contain an organic substance or an inorganic semiconductor, etc., in addition to MeO-TFATA.
[0072] Representative examples of organic substances used in the hole transport layer 6 include Spiro-OMeTAD, PTAA, poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT"), poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT") or copper phthalocyanine (hereinafter referred to as "CuPC").
[0073] An example of an inorganic semiconductor is Cu 2 O、CuGaO 2 、CuSCN、CuI、NiO x 、MoO x 、V 2 O 5 Or carbon materials like graphene oxide.
[0074] The hole transport layer 6 may include a plurality of layers formed of different materials. In this case, at least one layer includes MeO-TFATA.
[0075] The thickness of the hole transport layer 6 is preferably 1 nm to 1000 nm, and more preferably 10 nm to 500 nm. If the thickness of the hole transport layer 6 is 1 nm to 1000 nm, sufficient hole transport properties can be exhibited. Furthermore, if the thickness of the hole transport layer 6 is 1 nm to 1000 nm, the resistance of the hole transport layer 6 is low, so light can be efficiently converted into electricity.
[0076] The hole transport layer 6 may contain additives and solvents. The additives and solvents have the following effects, for example.
[0077] (i) The hole conductivity in the hole transport layer 6 is increased.
[0078] (ii) The photoelectric conversion layer 5 and the hole transport layer 6 are bridged to improve the efficiency of extracting holes.
[0079] (iii) Defect sites present on the surface of the photoelectric conversion layer 5 are inactivated.
[0080] Examples of additives include ammonium salts or alkali metal salts. That is, the hole transport layer 6 may also contain ammonium salts or alkali metal salts. Examples of ammonium salts include tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, or pyridinium salts. Examples of alkali metal salts include lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF 6 , LiBF 4 , lithium perchlorate or potassium tetrafluoroborate.
[0081] In order to improve the photoelectric conversion efficiency of the solar cell, the hole transport layer 6 preferably contains LiTFSI. By making the hole transport layer 6 further contain LiTFSI, the hole transport property of the hole transport layer 6 will be improved. As a result, the photoelectric conversion efficiency of the solar cell 100 is further improved. In the case where the hole transport layer 6 contains MeO-TFATA and LiTFSI, tert-butylpyridine (hereinafter referred to as "TBP") is preferably added to the hole transport layer 6. By adding TBP, the compatibility of MeO-TFATA and LiTFSI is improved. Thus, MeO-TFATA and LiTFSI are uniformly mixed, and the hole transport property of the hole transport layer 6 is further improved.
[0082] The concentration of the additive contained in the hole transport layer 6 is preferably 0.1 mmol / L to 100 mmol / L, more preferably 1 mmol / L to 10 mmol / L. When the concentration of the additive is 0.1 mmol / L to 100 mmol / L, the hole transport property of the hole transport layer 6 can be sufficiently improved.
[0083] The solvent contained in the hole transport layer 6 may have high ion conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilization of the solute, an organic solvent is preferred. Examples of organic solvents include heterocyclic compounds such as TBP, pyridine, or n-methylpyrrolidone.
[0084] The solvent contained in the hole transport layer 6 may be an ionic liquid. The ionic liquid may be used alone or in combination with other solvents. The ionic liquid is preferred in terms of low volatility and high flame retardancy.
[0085] Examples of the ionic liquid include imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds, or azobenzenium amine compounds.
[0086] like Figure 1 As shown, in the solar cell 100, the second electrode 2, the electron transport layer 3, the porous layer 4, the photoelectric conversion layer 5, the hole transport layer 6 and the first electrode 7 are sequentially stacked on the substrate 1. The solar cell 100 may not have the substrate 1. The solar cell 100 may not have the electron transport layer 3. The solar cell 100 may not have the porous layer 4.
[0087] (Substrate 1)
[0088] The substrate 1 holds the first electrode 7, the hole transport layer 6, the photoelectric conversion layer 5, the porous layer 4, the electron transport layer 3, and the second electrode 2. The substrate 1 can be formed of a transparent material. An example of the substrate 1 is a glass substrate or a plastic substrate. An example of a plastic substrate is a plastic film. When the second electrode 2 has sufficient strength, the second electrode 2 holds the first electrode 7, the hole transport layer 6, the photoelectric conversion layer 5, the porous layer 4, and the electron transport layer 3, so the solar cell 100 may not have the substrate 1.
[0089] (First electrode 7 and second electrode 2)
[0090] The first electrode 7 and the second electrode 2 are conductive. At least one electrode selected from the first electrode 7 and the second electrode 2 is light-transmissive. Light from the visible region to the near-infrared region can pass through the light-transmissive electrode. The light-transmissive electrode can be formed of a transparent and conductive material.
[0091] Examples of such materials mentioned above are:
[0092] (i) titanium oxide doped with at least one selected from lithium, magnesium, niobium and fluorine;
[0093] (ii) gallium oxide doped with at least one selected from tin and silicon;
[0094] (iii) gallium nitride doped with at least one selected from silicon and oxygen;
[0095] (iv) indium-tin composite oxide;
[0096] (v) tin oxide doped with at least one selected from antimony and fluorine;
[0097] (vi) zinc oxide doped with at least one of boron, aluminum, gallium and indium; or
[0098] (vii) Complexes thereof.
[0099] The light-transmitting electrode can be formed by using an opaque material and setting a pattern through which light is transmitted. Examples of patterns through which light is transmitted include linear, wavy, grid-like, or punched metal-like patterns in which a plurality of fine through holes are regularly or irregularly arranged. When the light-transmitting electrode has these patterns, light can pass through the portion where the electrode material is not present. Examples of opaque materials are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or alloys containing any of them. Conductive carbon materials can also be used as opaque materials.
[0100] When the solar cell 100 includes the electron transport layer 3 between the photoelectric conversion layer 5 and the second electrode 2, the second electrode 2 may not have a barrier property against holes from the photoelectric conversion layer 5. Therefore, the material of the second electrode 2 may be a material capable of ohmic contact with the photoelectric conversion layer 5.
[0101] In the case where the solar cell 100 does not include the electron transport layer 3, the second electrode 2 is formed of, for example, a material that has a blocking property against holes from the photoelectric conversion layer 5. In this case, the second electrode 2 is not in ohmic contact with the photoelectric conversion layer 5. The so-called "blocking property against holes from the photoelectric conversion layer 5" refers to the following property: only the electrons generated in the photoelectric conversion layer 5 are allowed to pass through, and holes are not allowed to pass through. The Fermi energy of the material that has a blocking property against holes is higher than the energy level at the upper end of the valence band of the photoelectric conversion layer 5. The Fermi energy of the material that has a blocking property against holes may also be higher than the Fermi energy of the photoelectric conversion layer 5. An example of a material that has a blocking property against holes is aluminum.
[0102] Since the solar cell 100 includes the hole transport layer 6 between the photoelectric conversion layer 5 and the first electrode 7 , the first electrode 7 may not have a blocking property against electrons from the photoelectric conversion layer 5 . In this case, the first electrode 7 may be in ohmic contact with the photoelectric conversion layer 5 .
[0103] The material that has a blocking property for holes from the photoelectric conversion layer 5 may not be light-transmitting. The material that has a blocking property for electrons from the photoelectric conversion layer 5 may not be light-transmitting. Therefore, when the first electrode 7 or the second electrode 2 is formed using these materials, the first electrode 7 or the second electrode 2 has the above-mentioned pattern such that light passes through the first electrode 7 or the second electrode 2.
[0104] The light transmittance of each of the first electrode 7 and the second electrode 2 may be 50% or more, or 80% or more. The wavelength of light transmitted through the electrodes depends on the absorption wavelength of the photoelectric conversion layer 5. The thickness of each of the first electrode 7 and the second electrode 2 is, for example, in the range of 1 nm to 1000 nm.
[0105] (Electron transport layer 3)
[0106] The electron transport layer 3 includes a semiconductor. The electron transport layer 3 is preferably formed of a semiconductor having a band gap of 3.0 eV or more. By forming the electron transport layer 3 using a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light can be transmitted to the photoelectric conversion layer 5. Examples of semiconductors include organic or inorganic n-type semiconductors.
[0107] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes or fullerene derivatives. Examples of inorganic n-type semiconductors are metal oxides, metal nitrides or perovskite oxides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO is preferred. 2 An example of a metal nitride is GaN. An example of a perovskite oxide is SrTiO 3 or CaTiO 3 .
[0108] The electron transport layer 3 may be formed of a material having a band gap greater than 6.0 eV. Examples of materials having a band gap greater than 6.0 eV are:
[0109] (i) halides of alkali metals or alkaline earth metals such as lithium fluoride or calcium fluoride;
[0110] (ii) an alkali metal oxide such as magnesium oxide; or
[0111] (iii) Silicon dioxide In this case, in order to ensure the electron transport property of the electron transport layer 3 , the thickness of the electron transport layer 3 may be, for example, 10 nm or less.
[0112] The electron transport layer 3 may include a plurality of layers made of materials different from each other.
[0113] (Porous layer 4)
[0114] The porous layer 4 facilitates the formation of the photoelectric conversion layer 5. The material of the photoelectric conversion layer 5 also intrudes into the inside of the pores of the porous layer 4. Therefore, the material of the photoelectric conversion layer 5 is less likely to be repelled or aggregated at the surface of the electron transport layer 3. Therefore, the porous layer 4 becomes the base of the photoelectric conversion layer 5, so that the photoelectric conversion layer 5 can be formed as a uniform film. The photoelectric conversion layer 5 can be formed by applying a solution on the electron transport layer 3 by spin coating and heating.
[0115] Light scattering is caused by the porous layer 4. Therefore, the optical path length of light passing through the photoelectric conversion layer 5 can be increased. The increase in the optical path length can increase the amount of electrons and holes generated in the photoelectric conversion layer 5.
[0116] The porous layer 4 is formed on the electron transport layer 3 by, for example, a coating method.
[0117] The porous layer 4 serves as a base for forming the photoelectric conversion layer 5. The porous layer 4 does not prevent electrons from moving from the photoelectric conversion layer 5 to the second electrode 2.
[0118] The porous layer 4 contains a porous body. An example of a porous body is a porous body formed by connecting insulating or semiconductor particles. Examples of insulating particles are aluminum oxide or silicon oxide. Examples of semiconductor particles are inorganic semiconductor particles. Examples of inorganic semiconductors are metal oxides (including perovskite oxides), metal sulfides or metal chalcogenides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO is preferred. 2 An example of a perovskite oxide is SrTiO 3 or CaTiO 3 Examples of metal sulfides are CdS, ZnS, In 2 S 3 、SnS、PbS、Mo 2 S.WS 2 , Sb 2 S 3 、Bi 2 S 3 、ZnCdS 2 Cu 2 S. Examples of metal chalcogenides are CdSe, CsSe, In 2 Se 3 ,WSe 2 , HgS, SnSe, PbSe or CdTe.
[0119] The thickness of the porous layer 4 is preferably 0.01 μm to 10 μm, more preferably 0.1 μm to 1 μm. In addition, the surface roughness of the porous layer 4 is preferably larger. Specifically, the surface roughness coefficient given by the effective area / projected area is preferably greater than 10, more preferably greater than 100. In addition, the projected area refers to the area of the shadow formed behind the object when light is irradiated from the front. The effective area refers to the actual surface area of the object. The effective area can be calculated based on the volume obtained from the projected area and thickness of the object and the specific surface area and volume density of the material constituting the object. The specific surface area is measured, for example, by nitrogen adsorption.
[0120] (Effects of solar cells)
[0121] Next, the basic effects of the solar cell 100 are described. When the solar cell 100 is irradiated with light, the photoelectric conversion layer 5 absorbs the light, so that excited electrons and holes are generated. The excited electrons move to the electron transport layer 3. On the other hand, the holes generated in the photoelectric conversion layer 5 move to the hole transport layer 6. The electron transport layer 3 and the hole transport layer 6 are electrically connected to the second electrode 2 and the first electrode 7, respectively. Current is taken out from the second electrode 2 and the first electrode 7, which function as a negative electrode and a positive electrode, respectively.
[0122] (Method of Manufacturing Solar Cell 100)
[0123] The solar cell 100 can be manufactured, for example, by the following method.
[0124] First, the second electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (hereinafter referred to as “CVD”) or sputtering.
[0125] The electron transport layer 3 is formed on the second electrode 2 by a coating method such as a spin coating method or a sputtering method.
[0126] On the electron transport layer 3 , the porous layer 4 is formed by a coating method such as a spin coating method.
[0127] The photoelectric conversion layer 5 is formed on the porous layer 4. The photoelectric conversion layer 5 can be formed, for example, as follows. 2 ) 2 Sn 3 (hereinafter referred to as "FASnI 3 ”) is described below.
[0128] First, SnI was added to the organic solvent. 2 and HC(NH 2 ) 2I (hereinafter referred to as "FAI") to obtain a mixed solution. An example of the organic solvent is a mixture (volume ratio = 1:1) of dimethyl sulfoxide (hereinafter referred to as "DMSO") and N,N-dimethylformamide (hereinafter referred to as "DMF").
[0129] Sn 2 The molar concentration can be 0.8 mol / L to 2.0 mol / L, or 0.8 mol / L to 1.5 mol / L.
[0130] The molar concentration of FAI may be 0.8 mol / L to 2.0 mol / L, or 0.8 mol / L to 1.5 mol / L.
[0131] Next, the mixed solution is heated to a temperature of 40°C to 180°C. By performing the above operation, a SnI 2 Then, the mixed solution was left at room temperature.
[0132] Next, the mixed solution is applied to the porous layer 4 by spin coating to form a coating film. Next, the coating film is heated at a temperature of 40° C. to 200° C. for 15 minutes to 1 hour. Thus, the photoelectric conversion layer 5 is formed. When the mixed solution is applied by spin coating, a poor solvent may be added dropwise during the spin coating process. Examples of the poor solvent are toluene, chlorobenzene or diethyl ether.
[0133] The mixed solution may contain a quencher substance such as tin fluoride, and the concentration of the quencher substance may be 0.05 mol / L to 0.4 mol / L. The quencher substance can suppress the generation of defects in the photoelectric conversion layer 5. The cause of the generation of defects in the photoelectric conversion layer 5 is, for example, due to Sn 4+ The increase in the amount of leads to an increase in Sn vacancies.
[0134] A hole transport layer 6 is formed on the photoelectric conversion layer 5. Examples of methods for forming the hole transport layer 6 are coating or printing. Examples of coating methods include a doctor blade method, a rod coating method, a spray method, a dip coating method, or a spin coating method. An example of a printing method is a screen printing method. It is also possible to mix a plurality of materials to obtain the hole transport layer 6, and then pressurize or sinter the hole transport layer 6. When the material of the hole transport layer 6 is an organic low molecular weight body or an inorganic semiconductor, the hole transport layer 6 can also be made by a vacuum evaporation method.
[0135] Finally, the first electrode 7 is formed on the hole transport layer 6. In this way, the solar cell 100 can be obtained. The first electrode 7 can be formed by using a CVD method or a sputtering method.
[0136] (Example)
[0137] The present disclosure is described in more detail with reference to the following examples.
[0138] [Example 1]
[0139] In Example 1, Figure 1 The solar cell 100 shown is manufactured in the following manner.
[0140] In the room, a SnO substrate 1 and a second electrode 2 were prepared. 2 The conductive glass substrate (manufactured by Geomatec Co., Ltd.) with a layer thickness of 1 mm. 2 The layers function as the substrate 1 and the second electrode 2 , respectively.
[0141] On the second electrode 2 , a titanium oxide layer having a thickness of about 10 nm is formed by sputtering. This titanium oxide layer functions as the electron transport layer 3 .
[0142] Next, the porous layer 4 is formed in a room as follows.
[0143] High-purity titanium oxide powder (manufactured by Great Cell Solar Co., Ltd.) having an average primary particle size of 30 nm was dispersed in ethyl cellulose to prepare a titanium oxide paste for screen printing.
[0144] A titanium oxide paste was applied on the second electrode 2 to form a coating film. The coating film was dried and then fired in air at 500° C. for 30 minutes. Thus, a porous titanium oxide layer with a thickness of 200 nm was formed. The porous titanium oxide layer functions as the porous layer 4 .
[0145] Next, in the glove box, SnI 2 (manufactured by Sigma Aldrich), SnF 2 (Sigma Aldrich) and FAI (GreatCell Solar). The solution contains SnI 2 、SnF 2 The concentrations of DMSO and FAI were 1.2 mol / L, 0.12 mol / L and 1.2 mol / L, respectively. The solvent of the solution was a mixture of DMSO and DMF (DMSO:DMF=1:1 (volume ratio)).
[0146] Then, the laminated body composed of the substrate 1 , the second electrode 2 , the electron transport layer 3 , and the porous layer 4 was transferred into a glove box.
[0147] In a glove box, 100 μL of the above solution was applied to the porous layer 4 by spin coating to form a coating film. The coating film had a thickness of 40 nm. A portion of the solution was also impregnated into the pores of the porous layer 4. Therefore, the thickness of the coating film included the thickness of the porous layer 4 (i.e., 200 nm).
[0148] The coating film was baked on a hot plate in a glove box at 80° C. for 30 minutes to form a photoelectric conversion layer 5. The photoelectric conversion layer 5 mainly contained a material having a chemical formula of FASnI 3 Perovskite compound represented by the chemical formula FASnI 3 The energy level of the lower end of the conduction band of the perovskite compound represented by is -3.5 eV based on the vacuum energy level. 3 The energy level at the upper end of the valence band of the perovskite compound shown is -4.9 eV based on the vacuum level.
[0149] In a glove box, a toluene solution containing MeO-TFATA (purchased from Auburn Laboratory Co., Ltd.) at a concentration of 12 mg / mL was prepared. The toluene solution containing MeO-TFATA was then applied onto the photoelectric conversion layer 5 by spin coating to form the hole transport layer 6 .
[0150] Finally, in the glove box, a gold film with a thickness of 100 nm was vapor-deposited on the hole transport layer 6 to form the first electrode 7. Then, it was sealed by clamping with glass (size: 20 mm square, thickness: 1.1 mm, manufactured by EHC Co., Ltd.). The sealed solar cell was taken out from the glove box. By performing the operation in this way, the solar cell of Example 1 was obtained. In addition, the following various measurements and calculations were performed indoors.
[0151] [Example 2]
[0152] A solar cell was obtained in the same manner as in Example 1 except for the following points in the step of preparing the toluene solution for forming the hole transport layer 6 .
[0153] (i) An acetonitrile solution of LiTFSI containing LiTFSI (manufactured by Sigma Aldrich) at a concentration of 170 mg / mL was prepared.
[0154] (ii) An acetonitrile solution containing the LiTFSI represented by (i), TBP (manufactured by Sigma Aldrich) and a toluene solution of MeO-TFATA (concentration of the acetonitrile solution of LiTFSI: 5.25 μL / mL, concentration of TBP: 6.17 μL / mL and concentration of MeO-TFATA: 12 mg / mL) was prepared. In addition, the solution prepared in (ii) was replaced with the toluene solution used in Example 1.
[0155] [Example 3]
[0156] A solar cell was obtained in the same manner as in Example 1 except for the following points in the preparation of the solution for forming the photoelectric conversion layer 5 .
[0157] (i) Preparation of SnI 2 (manufactured by Sigma Aldrich), SnF 2 (Sigma Aldrich), FAI (GreatCell Solar), and CH 6 N 3 I (hereinafter referred to as "GAI") solution (SnI 2 :1.2mol / L、SnF 2 :0.12mol / L, FAI: 1.0mol / L and GAI: 0.2mol / L).
[0158] (ii) The solvent prepared in (i) is a mixture of DMSO and DMF (DMSO:DMF=1:1 (volume ratio)).
[0159] The photoelectric conversion layer 5 in Example 3 mainly contains the chemical formula GA 0.17 FA 0.83 Sn 3 The perovskite compound represented by the chemical formula GA 0.17 FA 0.83 Sn 3 The energy level of the lower end of the conduction band of the perovskite compound represented by is -3.5 eV based on the vacuum energy level. 0.17 FA 0.83 Sn 3 The energy level at the upper end of the valence band of the perovskite compound shown is -4.9 eV based on the vacuum level.
[0160] [Example 4]
[0161] A solar cell was obtained in the same manner as in Example 3 except for the following points in the formation of the hole transport layer 6 .
[0162] (i) As the toluene solution used for forming the hole transport layer 6 , the toluene solution used in Example 2 was used.
[0163] [Comparative Example 1]
[0164] A solar cell was obtained in the same manner as in Example 1 except for the following points in the formation of the hole transport layer 6 .
[0165] (i) A toluene solution containing PTAA (obtained from Sigma Aldrich) at a concentration of 12 mg / mL was prepared instead of the toluene solution of MeO-TFATA. This toluene solution was used to form the hole transport layer 6 .
[0166] [Comparative Example 2]
[0167] A solar cell was obtained in the same manner as in Example 1 except for the following points in the step of preparing the toluene solution for forming the hole transport layer.
[0168] (i) An acetonitrile solution of LiTFSI containing LiTFSI (manufactured by Sigma Aldrich) at a concentration of 170 mg / mL was prepared.
[0169] (ii) A chlorobenzene solution containing the prepared LiTFSI in acetonitrile, TBP (manufactured by Sigma Aldrich) and Spiro-OMETAD was prepared (the concentration of the acetonitrile solution of LiTFSI: 17.5 μL / mL, the concentration of TBP: 20 μL / mL and the concentration of Spiro-OMETAD: 50 mg / mL). The solution prepared in (ii) was replaced with the toluene solution used in Example 1.
[0170] [Comparative Example 3]
[0171] A solar cell was obtained in the same manner as in Example 1 except for the following points regarding the toluene solution used to form the hole transport layer 6 .
[0172] (i) A toluene solution of P3HT containing P3HT (manufactured by Sigma Aldrich) at a concentration of 10 mg / mL was prepared instead of the toluene solution of MeO-TFATA. This toluene solution was used to form the hole transport layer 6 .
[0173] [Comparative Example 4]
[0174] A solar cell was obtained in the same manner as in Example 1 except for the following points in the step of preparing the toluene solution for forming the hole transport layer 6 .
[0175] (i) An acetonitrile solution of LiTFSI containing LiTFSI (manufactured by Sigma Aldrich) at a concentration of 170 mg / mL was prepared.
[0176] (ii) An acetonitrile solution containing the prepared LiTFSI, TBP (manufactured by Sigma Aldrich) and a toluene solution of P3HT (concentration of the acetonitrile solution of LiTFSI: 5.25 μL / mL, concentration of TBP: 6.17 μL / mL and concentration of P3HT: 10 mg / mL) was prepared. The solution prepared in (ii) was replaced with the toluene solution used in Example 1.
[0177] [Measurement of photoelectric conversion efficiency]
[0178] The solar cells of Examples 1 to 4 and Comparative Examples 1 to 4 were irradiated with a solar simulator ("OTENTO-SUN V Simulated Sunlight Device" manufactured by Spectrometer Corporation) having a power of 100 mW / cm 2 The open circuit voltage (Voc), short circuit current density (Jsc) and curve factor (FF) were calculated by using simulated sunlight with an illumination of . Next, the photoelectric conversion efficiency of each solar cell was calculated using the "relationship: conversion efficiency = (Voc × Jsc × FF) / (energy of incident light)" based on the values of Voc, Jsc and FF. Table 1 shows Voc, Jsc, FF and photoelectric conversion efficiency.
[0179] [Calculation of Energy Levels at the Lower End of the Conduction Band and the Upper End of the Valence Band of the Perovskite Compound Contained in the Photoelectric Conversion Layer 5]
[0180] In each of the examples and comparative examples, a sample was prepared which consisted of a substrate 1, a second electrode 2, an electron transport layer 3, a porous layer 4, and a photoelectric conversion layer 5. The sample did not include a hole transport layer 6 and a first electrode 7. That is, the surface of the photoelectric conversion layer 5 was exposed.
[0181] The energy level of the lower end of the conduction band of the perovskite compound contained in the photoelectric conversion layer 5 contained in the sample was measured by ultraviolet electron spectroscopy and transmittance measurement as described below.
[0182] Each sample was subjected to ultraviolet electron spectrometry using an ultraviolet electron spectrometer (manufactured by ULVAC PHI Co., Ltd., trade name: PHI5000VersaProbe) to obtain the energy level value of the upper end of the valence band of each tin-based perovskite compound.
[0183] Each sample was subjected to transmittance measurement using a transmittance measuring apparatus (manufactured by Shimadzu Corporation, trade name: SlidSpec-3700), and then the band gap value of each tin-based perovskite compound was obtained from the transmittance measurement results.
[0184] The energy level at the lower end of the conduction band of the perovskite compound is calculated from the energy level at the upper end of the valence band and the value of the band gap obtained as described above.
[0185] Table 1
[0186]
[0187] As can be seen from Table 1, the solar cells of Examples 1 to 4 have a photoelectric conversion layer 5 containing a tin-based perovskite compound and a hole transport layer 6 containing MeO-TFATA. Therefore, the solar cells of Examples 1 to 4 have a high photoelectric conversion efficiency exceeding 2.5%. On the other hand, the solar cells of Comparative Examples 1 to 4 have a photoelectric conversion layer 5 containing a tin-based perovskite compound and a hole transport layer 6 not containing MeO-TFATA. The solar cells of Comparative Examples 1 to 4 can only obtain a low photoelectric conversion efficiency of less than 1.2%.
[0188] As can be seen from the comparison of Example 2 with Example 1 and Example 4 with Example 3, a solar cell having a hole transport layer 6 in which LiTFSI is added to MeO-TFATA has a higher photoelectric conversion efficiency than a solar cell having a hole transport layer 6 to which LiTFSI is not added. On the other hand, as can be seen from the comparison of Comparative Example 4 with Comparative Example 3, in the case where LiTFSI is added to the hole transport layer 6 using other hole transport materials different from MeO-TFATA (i.e., P3HT in Comparative Examples 3 and 4) and not containing MeO-TFATA, the photoelectric conversion efficiency decreases. From these results, it can be seen that in tin-based perovskite solar cells, the effect of improving the photoelectric conversion efficiency by adding LiTFSI to the hole transport layer is achieved when the hole transport layer contains MeO-TFATA.
[0189] Industrial Applicability
[0190] The solar cell of the present disclosure is useful as a solar cell installed on a roof, for example.
[0191] Explanation of symbols
[0192] 1 substrate
[0193] 2. Second electrode
[0194] 3 Electron transport layer
[0195] 4 Porous layer
[0196] 5 Photoelectric conversion layer
[0197] 6 Hole Transport Layer
[0198] 7 1st electrode
[0199] 100 Solar Cells
Claims
1. A solar cell comprising: 1st electrode; The second electrode; a photoelectric conversion layer disposed between the first electrode and the second electrode; as well as a hole transport layer disposed between the first electrode and the photoelectric conversion layer, wherein at least one electrode selected from the first electrode and the second electrode has light-transmitting property, The photoelectric conversion layer contains a perovskite compound composed of a monovalent cation, a divalent cation, and a halogen anion, wherein the monovalent cation contains at least one selected from the group consisting of a formamidinium cation and a methylammonium cation. The divalent cations include Sn cations, The halogen anion comprises an iodide ion, The perovskite compound is composed of (HC(NH2)2)SnI3 or (CH6N3) 0.17 (HC(NH2)2) 0.83 SnI3 indicates that The hole transport layer contains 4,4',4"-tris[9,9-dimethyl-2-fluorenyl(4-methoxyphenyl)amino]triphenylamine.
2. The solar cell according to claim 1, wherein: The hole transport layer further contains an alkali metal salt.
3. The solar cell according to claim 2, wherein: The alkali metal salt is lithium bis(trifluoromethanesulfonyl)imide. 4 . The solar cell according to claim 1 , further comprising an electron transport layer provided between the second electrode and the photoelectric conversion layer.
Citation Information
Patent Citations
Photovoltaic element with improved long-term stability
JP2014520386A
Photovoltaic element with increased long-term stability
CN103636022A
Method for producing tin halide perovskite compound
JP2019038714A